Estudo da influência do gênero e idade nas alterações comportamentais e neuroquímicas induzidas pelo abrasamento por nicotina em ratos - Gomes, Patrícia Xavier Lima (2011)
Kindling is a well-known experimental model of progressive epilepsy induced by electrical or chemical subthreshold stimulation. Only recently nicotine-induced kindling was pharmacologicaly and histologicaly characterized. Furthermore is known sex and age differences in seizure susceptibility are one of the unresolved issues in epilepsy. Based on this, the present study aimed to investigate gender and age influences in behavioral and neurochemical changes nicotine-induced kindling in rats. Male and Female periadolescent (35-37 days old, n= 8/group) and adult (73-75 days old, n=8/group) Wistar rats were used. During 4 weeks, kindling seizures were induced by repeated administration of NIC 2.0 mg/kg, intraperitoneally, from Monday to Friday. Convulsant activity was evaluated according Racine scale. Thirty minutes after the last administration of NIC, animals were euthanized, prefrontal cortex (PFC), striatum (ST) and hippocampus (HC) dissected and homogenates to 10% prepared with potassium phosphate buffer (pH 7.4). Finally, homogenates were used to evaluate Superoxide Dismutase (SOD) activity, levels Glutathione Reduced (GSH) quantifying, nitrite/nitrate levels (as an indirect way to determine nitric oxide) and lipid peroxides formation by measuring the thiobarbituric-acid reacting substances (TBARS). Female periadolescent and adult and male adult presented same susceptibility to kindling development whem compared to male periadolescent, presented stage 5 seizures after 19 days NIC treatment, whereas male periadolescent rats presented stage 5 only after 24 days of administration. Regarding to deaths female periadolescente were more susceptible to toxic effects of NIC with 75% deaths in this group. Male periadolescent presented an increase in the GSH levels in CPF e CE and no change in SOD acitivity, nitrite content and lipid peroxidation. Unlike, other groups decreased GSH levels and SOD activitiy with membrane damage detected by an increase in lipid peroxidation in male adult and female periadolescent, but not in female adult animals. In conclusion, our results demonstrate that NIC-induced kindling is influenced by gender and age and oxidative stress parameters, are related, at least in part, to the animal’s susceptibility/resistance to the kindling induced by this drug.